Clarifying the presence of Pseudosuccinea columella (Say, 1817) (Gastropoda: Hygrophila: Lymnaeidae) in Serbia - Vukašin Gojšina; Mihailo Vujić (Malacologica Bohemoslovaca)
We report the first record of Pseudosuccinea columella (Say, 1817) from Serbia. This finding in the Tamiš River clarifies its presence in Serbia which was questioned in the 2021 checklist, as it was previously confused with succineid gastropods. The habitat is described in detail and its possible way of introduction is discussed.